2012
DOI: 10.1371/journal.pone.0052998
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Omega-3 Deficiency from Gestation Increases Spinal Cord Vulnerability to Traumatic Brain Injury-Induced Damage

Abstract: Although traumatic brain injury (TBI) is often associated with gait deficits, the effects of TBI on spinal cord centers are poorly understood. We seek to determine the influence of TBI on the spinal cord and the potential of dietary omega-3 (n-3) fatty acids to counteract these effects. Male rodents exposed to diets containing adequate or deficient levels of n-3 since gestation received a moderate fluid percussion injury when becoming 14 weeks old. TBI reduced levels of molecular systems important for synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…To our knowledge, this is the only research that has demonstrated remote lesions in the spine following mTBI. This may further help explain the impaired synaptic plasticity and reduced plasma membrane homeostasis in the lumbar spine as recently reported 6 . This has significant implications for future research and understand the distal muscular atrophy and complex regional pain symptoms often seen with patients following TBI.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…To our knowledge, this is the only research that has demonstrated remote lesions in the spine following mTBI. This may further help explain the impaired synaptic plasticity and reduced plasma membrane homeostasis in the lumbar spine as recently reported 6 . This has significant implications for future research and understand the distal muscular atrophy and complex regional pain symptoms often seen with patients following TBI.…”
Section: Discussionsupporting
confidence: 59%
“…Studies investigating how inflammation and maladaptive plasticity compromise spinal cord integrity at sites distant to the initial TBI are almost nonexistent. Zing et al, recently reported that TBI reduced levels of critical “molecular systems important for synaptic plasticity (BDNF, TrkB, and CREB) and plasma membrane homeostasis (4-HNE, iPLA2, syntaxin-3) in the lumbar spinal cord” 6 . Chen et al, showed that there are more distant neurodegenerative changes at sites uninvolved by the initial TBI, including increased neuronal degeneration and inflammation involving the ipsilateral hippocampus and thalamus between sham and injured groups who had received a mild controlled cortical contusion (CCI) 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Fluidity of plasma membrane plays important roles for cellular functions such as signal transduction, cell recognition, membrane order and the funtion of membrane receptors; flexibility of plasma membrane could increase membrane stability, which can adapt to challenge of different conditions (Lafourcade et al, ; Yamashima, ). The ratio of n‐3/n‐6 has a positive correlation with membrane fluidity and flexibility, which can be involved in antioxidative effects and upregulate the expression of antioxidant enzyme genes in NSCs Fat‐1 to enhance the capacity of scavenging ROS (Hasadsri et al, ; Lee et al, ; Ying, Feng, Agrawal, Zhuang, & Gomez‐Pinilla, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our work is consistent with several other studies where practice has improved performance on cognitive tasks, such as executive functioning and memory in military personnel (Bogdanova and Verfaellie, 2012). Additionally, both diet and exercise has been proven to be an effective remediation technique following TBI (Griesbach et al, 2009; Wu et al, 2011; Ying et al, 2012; Tyagi et al, 2013). Increased exercise in rodents within 2 days after injury improved cognitive deficits associated with object recognition memory (Chen et al, 2012) while an exercise regimen 3 months after injury improved working memory (Piao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%